EFFECTS OF GLIBENCLAMIDE ON ATP-SENSITIVE POTASSIUM CHANNELS IN CULTURED RAT DORSAL ROOT GANGLION NEURONES - Boydak, Erbil; Ayar, Ahmet (Fırat University, 2001)
Aims: This study was carried out to investigate the effects of glibenclamide on ATP-sensitive K,+ (K(ATP), channels in cultured rat sensory neurones. Material and Methods: Dorsal root ganglia (DRG) were removed after decapitation of neonatal Wistar rats and DRG neurones were isolated by enzymatic and mechanical procedures and incubated in a humidified incubator containing %95 CO2and air mixture at 37°C until being used for electrophysiological recordings. Whole-cell patch clamp techniques under current and voltage clamp configurations were used to record K (ATP) channel currents. Results: Membrane hyperpolarisation was observed depending on the application of glucose-free extracellular recording solution in the current-clamp experiments. Application of K(ATP) channel activator, diazoxide (100 µM) induced a membrane hyperpolarsation (mean -23+3.2 mV) in a similar manner which was completely blocked by glibenclamide (20 µM). Diazoxide (100 µM) activated outward membrane currents when used under the voltage-clamp experiments. This activation was inhibited by application of glibenclamide (20 µM, n=6). Conclusion: Results from this study indicates that glibenclamide blocks K(ATP) channel currents activated by both application of diazoxide and by the use of glucose-free extracellular recording solution.

Amaç:Bu çalışmanın amacı glibenklamidin sıçan duyusal sinir hücre kültürlerinde ATP duyarlı K+, (K(ATP)), kanallarına etkilerini incelemektir. Gereç ve Yöntem: Yenidoğan Wistar sıçanları dekapite edildi ve dorsal kök gangliyonları (DKG) enzimatik ve mekanik işlemlerle izole edildi ve elektrofizyolojik kayıtlar için kullanılıncaya kadar 37°C'de %95 karbondioksit, %5 hava karışımı içeren nemli bir inkübatörde tutuldu. Patch kenetleme tekniğinin tüm hücre diyaliz akım ve voltaj kenetleme varyasyonları kullanılarak K(ATP) kanal akımları kayıt edildi. Bulgular: Akım kenetleme deneylerinde, glikozsuz hücre dışı kayıt solüsyonu uygulamasına bağlı olarak membran hiperpolarizasyonu gözlendi. K(ATP) kanal aktivatörü diazoksid (100 µM) uygulanması da benzer şekilde bir membran hiperpolarizasyonu oluşturdu (ortalama -23±3.2 mili voltluk) ve glibenklamid (20 µM) bu membran hiperpolarizasyonlarını tamamen inhibe etti. Voltaj kenetleme deneylerinde hücrelere uygulanan diazoksid (100 µM) dışa yönelik membran akımlarını aktive etti ve bu aktivasyon glibenklamid (20 µM) uygulanmasıyla inhibe edildi (n=6). Sonuç: Bu çalışmanın bulguları sıçan DKG hücrelerinde glibenklamidin glikozsuz hücre dışı kayıt solüsyonu kullanılması veya diazoksitle aktive edilen K(ATP) kanal akımlarını blokladığını göstermektedir.
SIÇAN DORSAL KÖK GANGLİYON SİNİR HÜCRE KÜLTÜRLERİNDE GLİBENKLAMİDİN ATP-DUYARLI POTASYUM KANALLARINA ETKİSİ